THE EFFECT OF PEDAGOGICAL AND PROFESSIONAL COMPETENCE ON TEACHER PERFORMANCE THROUGH ECONOMIC LEARNING INNOVATION AS A MODERATING VARIABLE IN HIGH SCHOOL IN MAKASSAR CITY - Sintawati S; Thamrin Thahir; Muhammad Hasan (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The influence of pedagogical and professional competence on teacher performance through innovation in economics learning as a moderating variable in senior high schools in Makassar City. This study used a quantitative approach with Structural Equation Modeling (SEM) to test the causal relationship between variables. The results showed that professional competence had the greatest influence on learning innovation and teacher performance, followed by pedagogical competence. Learning innovation acted as a moderating variable that strengthened the influence of teacher competence on performance, although its contribution was relatively small. These results emphasize the importance of developing teacher competence in improving performance in senior high schools in Makassar City. There was a positive relationship between pedagogical and professional competence and teacher performance, and learning innovation as a moderating variable that influenced teacher performance. These findings emphasize the need for increased training and competency development for teachers to be able to innovate in learning. In addition, increasing learning innovation can be an effective strategy in improving student motivation and learning outcomes. This study provides important implications for educational policymakers to support the continuous strengthening of teacher competence. Thus, the development of competence and innovation in economics learning needs to be a top priority in efforts to improve the quality of education in senior high schools in Makassar City.